History of Studying of Electrification in Uzbekistan 40-60 th Years of XX Century - Gulzora Nematjonovna Saidboboeva (Peerian Journals Publishing, 2023)
During the Soviet era, many studies were created on the history of electrification, its role in social and economic life. It is noted that the important reform of electrification took a special place in the changes and updates of that period. The article analyzes the historiography of these works published in the Soviet period, most of which date from the 1940s to the 1960s and geographically cover the territory of present-day Uzbekistan
Keywords: history; historical literature; historiography